2020
DOI: 10.1002/app.48939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biodegradation of polylactic acid mineral composites in composting conditions

Abstract: In this study, the enhancement of the biodegradation rate of polylactic acid (PLA) filled with commercially available soil amendment product (NTM) or a nanoclay (Cloisite 25A) were evaluated. Cloisite 25A and NTM were incorporated into PLA at 5, 10, 20 (w/w) through melt blending. Transmission electron micrographs revealed particles with a wide range of sizes that were formed by clumping of many smaller particles. The particles showed good dispersion in PLA by scanning electron microscopy. Under standard compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Silva et al (2020a) composted PLA and starch biodegradable materials and observed cracks, pickles, and irregular surfaces early in the composting process. This change in the material's surface makes it more susceptible to biodegradation due to increased surface area and water permeation, accelerating hydrolysis (Flynn et al, 2020).…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Silva et al (2020a) composted PLA and starch biodegradable materials and observed cracks, pickles, and irregular surfaces early in the composting process. This change in the material's surface makes it more susceptible to biodegradation due to increased surface area and water permeation, accelerating hydrolysis (Flynn et al, 2020).…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Some authors have demonstrated that some particles catalyze biodegradation. Incorporating nano clays into PLA generally accelerates PLA biodegradation rate in composting conditions due to the clays’ high relative hydrophilicity, which can accelerate polymer hydrolysis 7–9 . According to Castro‐Aguirre, 7 the effect of the nano clays on the initial PLA molar mass during processing plays a crucial role in biodegradation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating nano clays into PLA generally accelerates PLA biodegradation rate in composting conditions due to the clays' high relative hydrophilicity, which can accelerate polymer hydrolysis. [7][8][9] According to Castro-Aguirre, 7 the effect of the nano clays on the initial PLA molar mass during processing plays a crucial role in biodegradation studies. Starch incorporation enhanced PLA biodegradation, as starch is hydrophilic and acts as a biological fuel for the growth of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has been investigated through various approaches. Several studies suggest the use of additives to accelerate PLA disintegration [ 32 , 33 , 34 , 35 , 36 , 37 ]. However, this strategy involves a trade-off between durability and degradability.…”
Section: Introductionmentioning
confidence: 99%